2020
DOI: 10.1108/bij-12-2019-0523
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the relationship between supply chain risk mitigation strategies and practices: an integrated approach

Abstract: PurposeThe purpose of this paper is to explore the relationship between various risk management strategies and risk management practices in order to design and hence enact a suitable supply chain risk mitigation (RM) plan. Additionally, this study proposes a hierarchical framework to explain the mutual relationship between supply chain risk management (SCRM) practices and strategies by considering the underlying dimensions between them.Design/methodology/approachAn amalgamation of systematic literature analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 106 publications
0
58
0
Order By: Relevance
“…Baryannis et al (2018b) generalized the definition of SCRM (after surveying prior definitions): “as a process that encompasses the collaborative and coordinated efforts of all parties involved in a SC to reduce vulnerability and increase robustness and resilience of the supply chain, ensuring profitability and continuity.” The various stages of SCRM process consist of identification, assessment, mitigation and monitoring of risks (Baryannis et al , 2018b). Risk classification and identification have been exhaustively discussed in the SCRM literature (Christopher and Peck, 2004; Wagner and Bode, 2008; Ghadge et al , 2013; Tarei et al , 2018). There is relatively less research that examines the effectiveness of alternative SCRM strategies in the different contextual environment (Chang et al , 2015; Ayağ et al , 2013).…”
Section: Literature Review and Methodologies Adoptedmentioning
confidence: 99%
See 4 more Smart Citations
“…Baryannis et al (2018b) generalized the definition of SCRM (after surveying prior definitions): “as a process that encompasses the collaborative and coordinated efforts of all parties involved in a SC to reduce vulnerability and increase robustness and resilience of the supply chain, ensuring profitability and continuity.” The various stages of SCRM process consist of identification, assessment, mitigation and monitoring of risks (Baryannis et al , 2018b). Risk classification and identification have been exhaustively discussed in the SCRM literature (Christopher and Peck, 2004; Wagner and Bode, 2008; Ghadge et al , 2013; Tarei et al , 2018). There is relatively less research that examines the effectiveness of alternative SCRM strategies in the different contextual environment (Chang et al , 2015; Ayağ et al , 2013).…”
Section: Literature Review and Methodologies Adoptedmentioning
confidence: 99%
“…The search results obtained from the review are used to explore various RMEs across heterogenous case industries (summarized in Table 2). The table excludes some review papers and articles which are based on the SC risk identification and assessment phase (like Baryannis et al , 2018b; Tarei et al , 2018; Ho et al , 2015) and merely focuses on different proactive and reactive RMEs (as per the definition in Section 1). Since SCRM as a domain gained momentum after the year 2000 (Baryannis et al , 2018b), it can be observed that all the articles appear in the range of the year 2000–2018.…”
Section: Literature Review and Methodologies Adoptedmentioning
confidence: 99%
See 3 more Smart Citations